Eksplorasi Kecerdasan Kinestetik Anak Sekolah Dasar Lewat Video Tari Tradisional Cempe - Grudhowaringin, Dhirgan (CV. Satria Jaya, 2025)
This study aims to describe dance learning in elementary schools using the Cempe dance video as a learning medium and to determine the stimulation of students' kinesthetic intelligence after using the media. The research employed a mixed-method approach: qualitative methods were used to describe the learning process, and quantitative methods with a one-group pretest-posttest design were applied to measure changes in students’ kinesthetic intelligence. The research subjects were first and second-grade students from two elementary schools in Malang and Blitar, totaling 30 students. Data were collected through observation and interviews using validated instruments, which showed a